Carbamazepine Induces Platelet Apoptosis and Thrombocytopenia Through Protein Kinase A - Xiao, Weiling; Zhou, Kangxi; Yang, Mengnan; Sun, Chenglin; Dai, Lan; Gu, Jian; Yan, Rong; Dai, Kesheng (Frontiers in Pharmacology, 2021)
Carbamazepine is extensively used worldwide to treat a wide range of disorders such as epilepsy, peripheral neuralgia and bipolar disorder. Thrombocytopenia and hemorrhage have been identified in multiple carbamazepine-treated patients. However, the underlying mechanism remains poorly understood. Here, we show that platelets undergo apoptosis after carbamazepine treatment. The apoptotic platelets induced by carbamazepine are rapidly removed in vivo, which accounts for thrombocytopenia. We found that carbamazepine treatment attenuates the phosphorylation level of BAD, vasodilator-associated stimulated phosphoprotein (VASP) and GPIbβ in platelets, indicating an inhibition effect on PKA. We further demonstrated that carbamazepine reduces PKA activity through PI3K/Akt/PDE3A signaling pathway. Pharmacological activation of PKA or inhibition of PI3K/Akt/PDE3A protects platelets from apoptosis induced by carbamazepine. Importantly, PDE3A inhibitors or PKA activator ameliorates carbamazepine-mediated thrombocytopenia in vivo. These ﬁndings shed light on a possible mechanism of carbamazepine-induced thrombocytopenia, designating PDE3A/PKA as a potential therapeutic target in the treatment of carbamazepine-induced thrombocytopenia.